The Role of Corporate Boards: A Roundtable Discussion of Where We're Going and Where We've Been. Issue 1 (6th April 2017) - Greene, Jesse; Gupta, Raj; L'Helias, Sophie; McCracken, Bill
Abstract : In this roundtable that took place at the 2016 Millstein Governance Forum at Columbia Law School, four directors of public companies discuss the changing role and responsibilities of corporate boards. In response to increasingly active investors who are looking to management and boards for more information and greater accountability, the four panelists describe the growing demands on boards for both competence and commitment to the job. Despite considerable improvements since the year 2000, and especially since the 2008 financial crisis, the clear consensus is that U.S. corporate directors must become more like owners of the corporation who "truly represent the long‐term interests of all of the shareholders." But if activist investors appear to pose the most formidable new challenge for corporate directors—one that has the potential to lead to shortsighted managerial decision‐making—there has been another, less visible development that should be welcomed by wellrun companies that are investing in their future growth as well as meeting investors' expectations for current performance. According to Raj Gupta, who serves on the boards of HewlettPackard, Delphi Automotive, Arconic, and the Vanguard Group, [O]ld‐fashioned institutional shareholders—many of them long‐term buyers and holders—now account for a remarkably large percentage of the ownership of U.S. companies. If you looked closely, I think you would find that, in every large U.S. public company today, as few as 20 large institutional shareholders control 50 to 75% of the stock. And although they're not activists who resort to the proxy process, they are also not the silent shareholders of the past . Although these investors are "bringing enormous pressure to bear on management, " the good news for managements and boards is that such concentration of ownership should make it far easier for them to build trust by making their case directly to "the investment community, " and so win the market support that can give companies the "breathing room" to carry out their long‐term business plans. Another piece of encouraging news for boards is that, by drawing on a more diverse pool of directors than in the past—one that includes a rapidly growing number of women, people of color, and "internationals"—they are finding themselves with a breadth of perspective and experience that has better prepared them to respond to changes in an increasingly global and volatile business environment.